KOMPOSISI DAN DOMINASI PATOTIPE Xanthomonas oryzae pv. oryzae, PENYEBAB PENYAKIT HAWAR DAUN BAKTERI PADA TANAMAN PADI DENGAN SISTEM PENGAIRAN BERBEDA DI KABUPATEN KARAWANG [The Composition and Domination of Xanthomonas oryzae pv. oryzae Pathotype, The Cause of Bacterial Leaf Blight on Rice Plants in Different irrigation System at Karawang District] - Yuliani, Dini; Natasuwirya, Sudir (BERITA BIOLOGI, 2017)
Bacterial leaf blight (BLB) is the major disease of rice caused by the bacteria Xanthomonas oryzae pv. oryzae (Xoo), that has various pathotypes making it difficult to control. This research was aimed to determine Xoo pathotype group in irrigated paddy fields with different of planting time based on differences of irrigation system in Jatiluhur Reservoir. The research was conducted in Karawang District the wet season (WS) of 2013/2014 and dry season (DS) of 2014 through survey and sampling of infected rice leaves of BLB. Isolation of Xoo bacte-ria was done in the laboratory by using dilution methods. Xoo pathotype test was carried out by inoculating Xoo isolate on five different varieties in Indonesian Center for Rice Researchâs green house, West Java. Observation of disease severity was done by measuring symp-toms of the disease that appeared at two and four weeks after inoculation. The disease severity of ?11% was classified as resistant (R), and for the disease severity of >11% was classified as susceptible (S). The results obtained a total of 602 Xoo isolates from rice plant samplings of irrigated rice fields in Karawang with irrigation systems I, II, III, and IV. At WS 2013/2014 was obtained 448 Xoo isolates consists of 29.69% of pathotype III; 40.85% of pathotype IV, and 29.46% of pathotype VIII. While, at DS 2014 was obtained 154 Xoo isolates consists of 1.95% of pathotype III, 53.25% of pathotype IV, and 44.80% of pathotype VIII. The areas with Type I of irrigation systems were domi-nated by Xoo pathotype IV in two cropping seasons. The areas with Type II of irrigation system dominated by Xoo pathotype IV in the wet season, while the dry season was dominated by Xoo pathotype VIII. The areas with Type III of irrigation system were dominated by Xoo pathotype III in the wet season, whereas during dry season was dominated by Xoo pathotype IV. The areas with Type IV of irrigation sys-tem were dominated by Xoo pathotype IV during wet season. Over all, in the dry season, Xoo pathotype IV was the dominant pathotype especially in irrigation systems Type I and IV. The dominance of Xoo pathotype can determine the resistant varieties that grown in the areas with different planting times on different irrigation systems.